Optimization of Lecturers' Understanding of OBE Curriculum and 4 Literacies (Human, Language, Data, Digital) at State University of Medan - Mansyur, Abil; Sinaga, Fajar Apollo; Firdaus, Muliawan; Octora, Maya; Marlan, Marlan; Siregar, Tiur Malasari (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
In the modern era of education, the implementation of the Outcome-Based Education (OBE) Curriculum and the mastery of four key literacies, human, language, data, and digital literacy are urgent needs for educators in higher education institutions. At the State University of Medan, lecturers' understanding of the OBE curriculum and these literacies is crucial for improving the quality of the learning process and student outcomes. This study aims to optimize the understanding of lecturers at the State University of Medan regarding the OBE curriculum and the required literacies to effectively integrate 21st-century skills into teaching and learning activities. The research employs a qualitative descriptive approach, using data collection techniques such as surveys, interviews, and focus group discussions (FGDs) involving 100 lecturers from various faculties at the State University of Medan. Data analysis was conducted using the triangulation method to obtain a comprehensive understanding of the lecturers’ levels of understanding and the challenges they face in implementing the OBE curriculum and the four literacies. The findings indicate that lecturers’ understanding of the OBE curriculum is varied, with some lecturers demonstrating a good grasp, while others require improvement in their knowledge and skills. Human and language literacies are relatively well-mastered by most lecturers; however, data and digital literacy remain challenges that need to be addressed. In conclusion, continuous professional development strategies, such as training and workshops, are required to enhance lecturers' understanding of the OBE curriculum and the four literacies. The implications of this study highlight the importance of institutional support in providing adequate resources and facilities, as well as encouraging collaboration among lecturers to strengthen pedagogical capabilities relevant to the demands of modern education.